Planejamento urbano & equipamentos comunitários : o caso de Passo Fundo/RS - Romanini, Anicoli (2007)
This present study tries to identify the community equipments of the city of Passo Fundo/RS, a medium-sized city located in the North of Rio Grande do Sul, as well as to evaluate if they grant the municipal demands according to the criteria established by the Law 6.766/1979, and by the authors who approach the subject. The work analyses the Community Equipments of public use of Health, Education, Security, Culture, Leisure and Sport, and it concentrates in their survey, in three sectors of the city, selected as a result of the available data about population, income level and purchasing power. The location, the implantation and the real dimension of the community equipments were compared to minimum parameters of reference, extracted from the bibliography researched about the theme. It was certified that the analyzed sectors have only the community equipments of health, education and security. It could also be observed that, the most part of the culture equipments implanted in the sectors are cultual and that they exist only one non public leisure equipment and two sportive ones, that do not carry out their social function, to a population of more than 23.000 inhabitants. In this sense, the work points out the importance and recommends the planning and adjustment of the Community Equipments in the sectors studied. The work still notes the necessity of deepen the theme for further studies, since that there are few authors who approach the theme, the legislation is little detailed and the parameters are very broad. Therefore, the contribution on the matters regarding the urban planning and, specially, to the community equipments, is a tool for the organized development of any city, since that it provides, above all, worthy conditions of housing to the towns in general. It is also seen that, the effective and concrete incorporation of the elements with relative relevance degree in the process of thinking about the urban planning and promoting the urbanization can effectively contribute for the urban citizen s quality of life, in obtaining a more balanced urban way, fairer, more diversified in the use of the equipments, with more quality of the spaces, specially those of public and community use